CHEMICAL COMPOSITION, ANTIOXIDANT AND ANTI-Candida albicans ACTIVITY OF ESSENTIAL OIL FROM THE LEAVES OF Juglans neotropica Diels “peruvian walnut” - Castro Luna, Américo (2024)
Introduction. - The "nogal peruano" is a large tree distributed in several regions of Peru, mainly in areas of late secondary and mature forests. Species supplying antioxidant essential oils are considered valuable for health applications. Essential oils with various constituents show synergistic effects and can be an effective alternative to prevent diseases.Objectives. - To evaluate the chemical composition, antioxidant and anti-Candida albicans activity of the essential oil of Juglans neotropica Diels leaves.Materials and methods. - The essential oil was obtained by steam distillation. Its chemical composition was analyzed by GC-MS analysis and its antioxidant activity was evaluated according to DPPH• and ABTS•+ methods. In addition, its anti-Candida albicans activity was determined, adapting protocols, using ketoconazole as a reference. The oil was diluted in DMSO and incubated with Candida albicans, measuring growth by 24-hour readings in 96-well microplates.Results. - Chemical composition analysis by GS-MS revealed the presence of compounds such as phytol, α-pinene, α-caryophyllene, copaene and D-limonene. According to the DPPH• method, the essential oil showed an IC50 of 52.25 ul/ml. With the ABTS•+ method the IC50 was 34.65 ul/ml. However, no anti-Candida albicans activity was observed.Conclusion. - The most important chemical compounds of the essential oil of Juglans neotropica Diels leaves were α-pinene, D-limonene and Copaene. In addition, it presented regular antioxidant activity and null anti-Candida albicans activity.